2006
DOI: 10.2310/7060.2005.12306
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Primaquine for Vivax Malaria

Abstract: The available data presented here suggest that vivax malaria in this region is increasingly tolerant of the 22.5 mg daily treatment regimen of primaquine and that the greater dose of at least 30 mg daily is more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Notwithstanding these encouraging findings, caution needs to be exercised because P. vivax relapses may occur up to more than six months after acute infections and that a higher dose of primaquine (30 mg/day for 14 days) might have prevented more relapses. 3 The patient relapsing in this study after chloroquine and tafenoquine treatment had markedly lower plasma tafenoquine concentrations for the first six weeks after commencing tafenoquine treatment compared with those who where successfully treated with the drug combination. His low plasma tafenoquine concentrations suggest that he experienced difficulty in absorbing the drug after the commencement of treatment.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Notwithstanding these encouraging findings, caution needs to be exercised because P. vivax relapses may occur up to more than six months after acute infections and that a higher dose of primaquine (30 mg/day for 14 days) might have prevented more relapses. 3 The patient relapsing in this study after chloroquine and tafenoquine treatment had markedly lower plasma tafenoquine concentrations for the first six weeks after commencing tafenoquine treatment compared with those who where successfully treated with the drug combination. His low plasma tafenoquine concentrations suggest that he experienced difficulty in absorbing the drug after the commencement of treatment.…”
mentioning
confidence: 64%
“…These infections required increasing doses of primaquine to adequately prevent relapse. 3 In an effort to eliminate these primaquine-tolerant parasites, we evaluated chloroquine and an extended treatment course of tafenoquine (formerly known as WR 238605), a primaquine analog, to see whether such a regimen would be more efficacious than chloroquine and primaquine. We report the effectiveness and tolerability of this open-label, prospective use of tafenoquine given over 8 weeks as treatment for P. vivax malaria after a standard course of chloroquine (1,500 mg total dose) to treat the acute attack.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Duarte et al [15] in Cuiaba, Brazil and Kitchener et al [16] in Melbourne, Australia, prospectively followed patients for two years and showed relapse rates of 14% in 50 patients and 24% in 318 patients, respectively. The higher frequency recorded (40%) could be explained by the smaller sample in this study or by the fact that data for Brazil obtained in 2005-2011 were compared to data obtained in 1991 and in 2003, and concern with primaquine tolerance may have been different in these two periods.…”
Section: Discussionmentioning
confidence: 99%
“…Although Luxemburger et al (137) found a 91% efficacy of 15 mg daily for 14 days with 2 months of follow-up, Walsh et al (232) and Pukrittayakamee et al (174) measured efficacies of that regimen to be 69% and 42%, respectively. Standard 14-day therapy of 15 mg daily failed more often than either the 22.5-or 30-mg daily regimen (34,174), and the 22.5-mg daily regimen failed more often than did the 30-mg daily regimen (117). Likewise, a 30-mg daily dose works better when given for 11 or 14 days than when given just 5, 7, or 9 days (127).…”
Section: Distributionmentioning
confidence: 99%